Open Process 22 January 1969 - San Francisco State University - Associated Students (San Francisco State University - Associated Students, 1969)
Open Process for the academic year 1968-1969 was published every other week by the Board of Publications for the Associated Students of San Francisco State College, by this time it was suspended as an independent publication (by order of President John Summerskill on November 29, 1967) and printed as a supplement to the Daily Gater. This student newspaper offered a more radical perspective spotlighted campus news and events and includes advertisements.